2014
DOI: 10.1063/1.4891626
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni waves in a two-layer film under the action of an inclined temperature gradient

Abstract: The development of the longwave deformational instability of a thermocapillary flow in a two-layer film under the action of an inclined temperature gradient is studied in the framework of the lubrication approximation. The stability boundaries with respect to different oscillatory modes are calculated by means of the linear stability theory. In a contradistinction to the case of a vertical temperature gradient, these boundaries strongly depend on the direction of the wave propagation. Numerical simulations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…In the case of a fixed temperature gradient at the substrate, Davis (1987) showed that there exists a relationship between the critical Marangoni numbers defined using the imposed HTG and VTG, which did not predict the stabilization caused by the imposed HTG. However, the later studies of Nepomnyashchy, Simanovskii & Braverman (2001) and Shklyaev & Nepomnyashchy (2004) and the present work show that a prescribed HTG has a strong stabilizing effect on the modes found by Pearson (1958) which are caused by the prescribed VTG. Furthermore, Davis (1987) showed a negligible effect on the surface-wave instabilities at low Prandtl numbers Pr.…”
Section: Introductioncontrasting
confidence: 40%
See 3 more Smart Citations
“…In the case of a fixed temperature gradient at the substrate, Davis (1987) showed that there exists a relationship between the critical Marangoni numbers defined using the imposed HTG and VTG, which did not predict the stabilization caused by the imposed HTG. However, the later studies of Nepomnyashchy, Simanovskii & Braverman (2001) and Shklyaev & Nepomnyashchy (2004) and the present work show that a prescribed HTG has a strong stabilizing effect on the modes found by Pearson (1958) which are caused by the prescribed VTG. Furthermore, Davis (1987) showed a negligible effect on the surface-wave instabilities at low Prandtl numbers Pr.…”
Section: Introductioncontrasting
confidence: 40%
“…Thermocapillary instability in the fluid layers subjected to OTG has been previously studied by Nepomnyashchy et al (2001) and Shklyaev & Nepomnyashchy (2004) for a return flow configuration. They considered a two-layer structure of the fluids with the fluid-fluid interface assumed to be non-deformable.…”
Section: Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, up to now, most of the interest about thermocapillary-buoyancy convection in a two-layer liquid system is related to vertical heating. This type of convection is called the Rayleigh-Bénard convection or the Rayleigh-Bénard-Marangoni convection, which correspond to two-layer systems with or without an upper free surface, respectively [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%